Correction: Sgherza et al. Efficacy and Safety of Isatuximab, Carfilzomib, and Dexamethasone (IsaKd) in Multiple Myeloma Patients at the First Relapse After Autologous Stem Cell Transplantation and Lenalidomide Maintenance: Results from the Multicenter, Real-Life AENEID Study. Pharmaceuticals 2025, 18, 595 - Nicola Sgherza; Olga Battisti; Paola Curci; Concetta Conticello; Salvatore Palmieri; Daniele Derudas; Candida Germano; Enrica Antonia Martino; Giuseppe Mele; Roberta Della Pepa; Francesca Fazio; Anna Mele; et al. (Pharmaceuticals, 2025)
In the original publication [...]